Effect of seaweed liquid fertilizer on the germination and growth of seedling of mangrove - Rhizophora mucronata Boir - P. Perumal, T. Nedumaran, (Journal of Phytology, 2009)
Seaweeds are among the important marine living resources with tremendous commercial application. The effect of sea weed liquid fertilizer of Padina boergesenii was studied on the growth parameters of Rhizophora mucronata. Ã‚Â The propagules were soaked in different concentrations (0.5, 1, 1.5 and 2%). Within 24 hours soaking, all the soaked propagules were carefully planted in individual polythene bags each containing 2 kg of soil best response was found after 90 days at 1% concentration of seaweed extract in almost all the growth parameters. The maximum growth was recorded at 1% concentration Viz.,shoot length 24.3 cm, leaf breadth 3.45 cm, leaf length 7.1 cm when compared to control (13.7 cm shoot length, leaf breadth 3.0 cm and leaf length 5.35 cm). It was concluded that differential response was noticed in the mangrove plant to the seaweed extract treatment. In spite of these differential responses, Padina boergesenii was found to be an effective seaweed liquid fertilizer (SLF) in mangrove plant.